A Stiff yet Rapidly Self‐Healable Elastomer in Harsh Aqueous Environments. (1st October 2021) - Chen, Lili; Feng, Wenwen; Li, Mengxue; Jin, Zhekai; Zhang, Yucheng; Cheng, Zhe; Liu, Yuncong; Wang, Chao
Abstract: Rapid underwater self‐healing elastomers with high mechanical strength at ambient temperature are highly desirable for dangerous underwater operations. However, current room temperature self‐healing materials have shortcomings, such as low healing strength (below megapascal), long healing time (hours), and decay of healing functions in harsh environments (salty, acidic, and basic solutions), limiting their practical applications. Herein, it is introduced water‐stable Debye forces and high‐density nano‐sized physical crosslinking into one network to achieve a stiff yet rapid self‐healing elastomer that can work in harsh aqueous environments. The obtained elastomer possesses a high Young's modulus of 48 MPa (24 times than that of natural elastomer), and it can achieve 90% of maximum mechanical strength healing for 10 s at ambient temperature in all types of harsh aqueous conditions, outperforming three orders of magnitudes in healing speed of reported room‐temperature self‐healing elastomers with Young's modulus over 10 MPa. The new stiff yet rapidly healable elastomers have great potential in emergent repair in urgent and dangerous cases. Abstract : A stiff PBMA‐PEA rubber (≈48 MPa) with rapid self‐healing capability (achieve 90% of maximum mechanical strength healing for 10 s) is obtained by incorporating high‐density nano‐sized physical crosslink and water‐stable Debye forces, which have great potential in emergent repair in urgent and dangerous cases. A novel aqueous self‐healing mechanism, which is unaffected by acids, bases, and salts, is also proposed.